The congruence between teacher and student personality type and student achievement - 356429 Hart, Denise ([S.l.] : Rutgers University, The State University of New Jersey (New Brunswick), 1984)
Thesis (Ed. D.) - Rutgers University, The State University of New Jersey (Brunswick), 1984